The Relationship between Social Support and Subjective Well-Being: A Meta-Analysis - Nur Hikmah; Erwin Erlangga; Lucia Rini Sugiarti (Journal Social Civilecial, 2026)
Subjective well-being is an important indicator of individuals’ quality of life, and social support is often considered a contributing factor in enhancing it. However, empirical findings regarding the relationship between these variables remain inconsistent. Therefore, this study aims to comprehensively examine the relationship between social support and subjective well-being using a meta-analytic approach.This study employed a meta-analysis method by integrating six empirical studies obtained from the Scopus database within the 2020–2026 period, with a total sample of 3,087 participants. The analysis was conducted using a random-effects model with the assistance of JASP software. All effect sizes were transformed into Fisher’s Z to improve variance stability. The results indicate that the relationship between social support and subjective well-being tends to be positive but weak and statistically non-significant (pooled effect = 0.137; p > 0.05). In addition, a very high level of heterogeneity was found (Q = 565.92; p < 0.001; τ² = 0.237), along with a wide prediction interval, indicating instability of effects across studies. Variations in the direction of relationships, including negative effects in some studies, suggest that social support does not consistently function as a protective factor for subjective well-being.